THE USE AND CHALLENGES OF CLOUD COMPUTING SERVICES ADOPTION AMONG SMES IN NIGERIA - Ofili, Onyeka Uche (European Scientific Journal, ESJ, 2015)
This paper considers the factors militating against the ready adoption of cloud services by Small and Medium Enterprises (SMEs) in Nigeria. The paper recognizes that the major challenges affecting the adoption of cloud services in Nigeria include infrastructural issues such as lack of adequate and affordable Internet network facilities and unstable power supply. Other factors include lack of proper awareness of the benefits of cloud services, high cost of bandwidth, and high cost of supporting cloud services among others. To mitigate these problems it is suggested that private organizations should make more investment in Information and Communications Technology (ICT) infrastructure in Nigeria and government on its part should create the enabling environment for this to be achieved. Private and public institutions alike should increase effort to encourage SMEs to understand the benefits of adopting cloud services to their bottom-line. Other ways the adoption of cloud services can be improved include the establishment of more focused research in the area of cloud computing; private organizations and possibly government can sponsor such researches. Furthermore, regulation including enforcement of data protection laws and all other intellectual property rights protection regime should be adequately enforced. If all these challenges are resolved cloud computing has the potential to be the next big thing in Nigeria and revolutionize the profitability of SMEs.